2007
DOI: 10.1016/j.brainres.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Nociception in fish: stimulus–response properties of receptors on the head of trout Oncorhynchus mykiss

Abstract: This study examined stimulus-response properties of somatosensory receptors on the head of rainbow trout, Oncorhynchus mykiss, using extracellular recording from single cells in the trigeminal ganglion. Of 121 receptors recorded from 39 fish, 17 were polymodal nociceptors, 22 were mechanothermal nociceptors, 18 were mechanochemical receptors, 33 were fast adapting mechanical receptors and 31 were slowly adapting mechanical receptors. Mechanical thresholds were higher in polymodal nociceptors than in either slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 26 publications
(43 reference statements)
4
106
0
1
Order By: Relevance
“…The receptor types of trigeminal neuron for rainbow trout were found to correspond with those identified in a teleost fish [45] who defined them as polymodal and mechanothermal nociceptors. However, there is an apparent absence of cold nociceptors in the head region of trout [46]. The present experiment supports the former report.…”
Section: Discussionsupporting
confidence: 92%
“…The receptor types of trigeminal neuron for rainbow trout were found to correspond with those identified in a teleost fish [45] who defined them as polymodal and mechanothermal nociceptors. However, there is an apparent absence of cold nociceptors in the head region of trout [46]. The present experiment supports the former report.…”
Section: Discussionsupporting
confidence: 92%
“…In this sense, the goldfish (Carassius auratus) and rainbow trout (Oncorhynchus mykiss) have been reported to present nociceptors that respond to mechanical, thermal, and chemical stimulations (Sneddon 2003a, Dunlop & Laming 2005, Ashley et al 2007) and morphine reduced dramatically the behavioral and physiological responses after injection of a noxious stimulus (Sneddon 2003b). As a teleost fish, zebrafish, has an analgesic system, opioid system (Gonzalez-Nunez & Rodriguez 2009), and according to our findings, this organism also has the receptor of SP, Tacr1a and Tacr1b.…”
Section: Discussionmentioning
confidence: 99%
“…It can be deduced that this organism through this nociceptive and tachykinin system can feel pain. Unfortunately, at present, a prototypic behavioral pain model in zebrafish has not been developed, as in mouse and rat, to corroborate the molecular and electrophysiological findings of pain in fishes (Sneddon 2003a, Dunlop & Laming 2005, Ashley et al 2007. However, all the recent studies using the zebrafish as a model point to this organism as a new potential model in the study of pain.…”
Section: Discussionmentioning
confidence: 99%
“…When first describing cutaneous nociceptors in rainbow trout, Sneddon (Sneddon, 2002) found that some trigeminal nociceptors innervating the facial region responded to topical application of 1.0% acetic acid. However, Ashley et al (Ashley et al, 2007) applied acetic acid to chemoreceptors, and found no receptor response to 0.1% and 0.5% acetic acid. These findings demonstrate that the chemosensory receptors of trout are activated to some degree by acetic acid and possibly in a concentration-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Acetic acid was chosen as this algesic has been validated as a noxious stimulus in trout (Sneddon, 2002;Sneddon, 2003;Sneddon et al, 2003;Ashley et al, 2006;Ashley et al, 2007). Increasing concentrations of acetic acid were applied to the receptive fields of polymodal nociceptors and mechanochemical afferents.…”
Section: Introductionmentioning
confidence: 99%